Inward hunger : the story of Eric Williams - conversations with alumni - Pilgrim, Alake (2011)
Provides a compilation of thoughts from some of the UWI's leading academic minds on the contribution of Dr. Eric Williams for documentary series "Inward Hunger : The Story of Eric Williams," produced and directed by UWI alumna Mariel Brown; produced with the support of the Government Information Services Ltd (GISL), First Citizens, and the Trinidad and Tobago Film Company.